Video Application Model in Students’ Learning Style for Moral Education in Teacher Education Institutes - Razimi Bin Husin, Mohd; Bin Ahmad, Hishamuddin; Bin Hamzah, Mahizer (International Journal of Engineering and Technology, 2018)
The purpose of this study is to explore the specific trends and situations in video use to accomodate the learning styles of moral education students in Teacher Education Institutes. This is a case study in where data were collected through interviews. This study was conducted on six students. Semester four students were chosen through purposive sampling from two Teacher Education Institutes in Malaysia. The construct and internal validity were verified by experts while the external validity verification was supported by the findings from other studies with existing theories. Data of the study were analyzed by applying constant comparison techniques of the use of digital devices using the Nvivo software. This comparison is to identify the themes of the use of video, and its characteristics, and needs of students. The Multisensory Instructional Packages (MIPs) of Dunn and Dunn Learning Styles Model were used as guidance in the interviews because these packages was the most suitable to be applied to students with multisensory element. The results of the analysis showed that the use of videos need to address three aspects which include the factors that affected students’ tendency to watch video in learning, types of video, and video effects that enabled students to memorize the content knowledge and  participate in the discussions of  the topic taught. The research had produced a model on video use to accommodate the learning styles of moral education students in Teacher Education Institutes which could be used by instructors in their professional practice in the lecture room.
Keywords: Video; Learning Styles; Moral Education; Multi-sensory Element; Dunn and Dunn Learning Styles Model.